2016
DOI: 10.1007/s13277-016-5300-y
|View full text |Cite
|
Sign up to set email alerts
|

Association between XRCC3 Thr241Met polymorphism and nasopharyngeal carcinoma risk: evidence from a large-scale case-control study and a meta-analysis

Abstract: The X-ray repair cross-complementing group 3 (XRCC3) Thr241Met polymorphism (rs861539, C > T) has drawn wide attentions as its association with cancer risk and its involvement in DNA repair. Several studies have attempted to link rs861539 to nasopharyngeal cancer (NPC) risk; however, the sample sizes of these studies are small and the results are controversial. To investigate the relationship of rs861539 and NPC susceptibility, we conducted a large-scale case-control study involving 4001 NPC cases and 2967 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…S1 " type="url"/> ), but all cultures demonstrated significant expression of KRT genes consistent with epithelial origin. No known pathogenic cancer mutations or driver genes were identified; however, cancer risk-related probable pathogenic SNPs were reproducibly present in both of the four paired samples subjected to exome sequencing ( ; Agalliu et al, 2010 ; Alvarez-Cubero et al, 2016 ; Cheng et al, 2014 ; Chou et al, 2017 ; Cui et al, 2016 ; Dai et al, 2014 ; Dong et al, 2016 ; Ewart-Toland et al, 2005 ; Guo et al, 2014 ; Hu et al, 2014 ; Huang and Yang, 2015 ; Jiao et al, 2012 ; Johnson et al, 2007 ; Tanaka et al, 2010 ; Tian et al, 2017 ; Xu et al, 2015 ; Yan et al, 2016 ). In GUMC220/221, these included Brca2 rs144848 , TP53 rs1042522, AURKA rs2273535, RET rs1800858 and ADH1B rs1229984.…”
Section: Resultsmentioning
confidence: 99%
“…S1 " type="url"/> ), but all cultures demonstrated significant expression of KRT genes consistent with epithelial origin. No known pathogenic cancer mutations or driver genes were identified; however, cancer risk-related probable pathogenic SNPs were reproducibly present in both of the four paired samples subjected to exome sequencing ( ; Agalliu et al, 2010 ; Alvarez-Cubero et al, 2016 ; Cheng et al, 2014 ; Chou et al, 2017 ; Cui et al, 2016 ; Dai et al, 2014 ; Dong et al, 2016 ; Ewart-Toland et al, 2005 ; Guo et al, 2014 ; Hu et al, 2014 ; Huang and Yang, 2015 ; Jiao et al, 2012 ; Johnson et al, 2007 ; Tanaka et al, 2010 ; Tian et al, 2017 ; Xu et al, 2015 ; Yan et al, 2016 ). In GUMC220/221, these included Brca2 rs144848 , TP53 rs1042522, AURKA rs2273535, RET rs1800858 and ADH1B rs1229984.…”
Section: Resultsmentioning
confidence: 99%
“…Results restricted to Asians were similar. A separate evaluation of the Thr241Met polymorphism in XRCC3 reported a meta-OR of 3.1 under the recessive model, based on four NPC case-control studies in Asians (186).…”
Section: Candidate-gene Studiesmentioning
confidence: 99%
“…The etiology of NPC is a multifactorial process, involving genetic, viral, and environmental factors [2]. Large-scale case-control association studies and familial linkage studies have confirmed the genetic contribution to NPC predisposition, by revealing multiple susceptibility loci of NPC, such as HLA genes [36], TNFRSF19 [5], MECOM [5], GABBR1 [3], XRCC3 [7], ITGA9 [4], TERT-CLPTM1L [810], and CIITA [8]. However, these explain only a small fraction of the NPC heritability [11, 12].…”
Section: Introductionmentioning
confidence: 99%